Comparative Hepatoprotective Effects of Carica papaya, Azadirachta indica, and Allium sativum Extracts against Diethyl Nitrosamine-Induced Liver Injury in Wistar Rats - Egeonu US; Umaru I.J; Izam ED; Umaru K.I; Shadrach P (African Journal of Clinical Medicine and Pharmacy Research, 2026)
Diethylnitrosamine (DEN) induces oxidative stress, lipid peroxidation, and hepatocellular damage, highlighting the need to identify effective hepatoprotective agents. Although Carica papaya, Azadirachta indica, and Allium sativum possess recognized antioxidant and anti-inflammatory potential, evidence regarding their combined hepatoprotective effects remains limited. This study compared the effects of their individual and combined extracts against DEN-induced liver injury in male albino Wistar rats. Rats weighing 150–200 g were allocated to six groups (n = 6): normal control, DEN-only, papaya extract, neem extract, garlic extract, and combined-extract groups. DEN was administered intraperitoneally at 100 mg/kg once weekly for eight weeks. Ethanolic plant extracts prepared through Soxhlet extraction were administered orally at doses ranging from 100 to 400 mg/kg daily. Serum alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, bilirubin, malondialdehyde, and glutathione concentrations were assessed using standard biochemical assays, while liver tissues were evaluated histologically following hematoxylin and eosin staining. Data were analyzed using analysis of variance followed by Tukey’s post hoc test, with statistical significance established at p < 0.05. DEN exposure significantly increased liver enzymes, bilirubin, and malondialdehyde while reducing glutathione, confirming substantial hepatic injury. The individual extracts provided moderate protection, as demonstrated by partial normalization of biochemical markers and improved histological features. Hepatoprotection increased with dosage, with the strongest effects observed at 300–400 mg/kg. The combined extract produced the greatest protective effect, with biochemical indices approaching normal control values, improved antioxidant status, and restoration of hepatic architecture. These findings indicate that combining papaya, neem, and garlic extracts may provide greater hepatoprotection than administering the individual extracts against DEN-induced liver injury. The study supports further mechanistic and preclinical evaluation of this polyherbal formulation before its potential therapeutic application in liver-disease management.